2005
DOI: 10.1016/j.febslet.2005.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Significant species‐dependence of P700 redox potential as verified by spectroelectrochemistry: Comparison of spinach and Theromosynechococcus elongatus

Abstract: The redox potentials of P700, the primary electron donor of photosystem (PS) I, of spinach and Thermosynechococcus elongatus were determined by means of spectroelectrochemistry with an error range of ±2-3 mV, to find that the redox potential of P700 in T. elongatus is lower by ca. 50 mV as compared with spinach. The shift in the P700 redox potential of PS I core particles prepared by harsh detergent treatments remained to within 10 mV for both organisms. These results show that the 50 mV difference in the P700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 14 publications
2
28
1
Order By: Relevance
“…Hu et al (20) reported that the redox potential of P740 was 335 mV. This is significantly lower than that of the T. elongatus PS I (ϩ423 mV) (22,23) and of PS I from other species (24), and it is inconsistent with recent studies of P740 in A. marina (25,26).…”
Section: Photochemically Active Photosystem (Ps)contrasting
confidence: 53%
See 2 more Smart Citations
“…Hu et al (20) reported that the redox potential of P740 was 335 mV. This is significantly lower than that of the T. elongatus PS I (ϩ423 mV) (22,23) and of PS I from other species (24), and it is inconsistent with recent studies of P740 in A. marina (25,26).…”
Section: Photochemically Active Photosystem (Ps)contrasting
confidence: 53%
“…Speculating that the main cause for the discrepancy is the low accuracy of chemical titration (22,23,42), the spectroelectrochemical method was adopted in this study. The redox potential values were deduced from the five bands seen in the difference spectra, at 692, 710, 728, 740, and 820 nm (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of 6 mV for the determination of E m (Phe a/Phe a Ϫ ) seems to be rather large (seen in Fig. S2), especially compared with our previous measurements on redox species in PS I and II yielding values within an error range of Ϯ2 mV (27)(28)(29)(30)(31); this might be partially due to an interference from irreversible photoreactions of peripheral species during photoaccumulation of Phe a Ϫ . The E m (Phe a/Phe a Ϫ ) determined in the present work is by as much as Ϸ100 mV positive of those reported in 1978-1981, namely Ϫ610 Ϯ 30 mV by Klimov et al…”
Section: Discussionmentioning
confidence: 91%
“…These features enabled us to determine the redox potential E m of P700 (primary donor in PS I) and other components to within Ϯ2 mV (27)(28)(29)(30)(31) and to unveil the species dependence of the E m value of P700 (28,29). This has been extended in the present work to measure the E m (Phe a/Phe a Ϫ ) value in PS II complexes at physiological pH, by overcoming several difficulties inherent in the strongly negative potential range.…”
mentioning
confidence: 84%